Effects of alcohol intake in periodontitis progression in female rats: A histometric study - de Souza, Daniela Martins; Ricardo, Lucilene Hernandes; da Rocha, Rosilene Fernandes [UNESP] (My University, 2014)
Aim: To evaluate histometrically the effect of low and high caloric value of ethanol on ligatureinduced bone loss in female rats. Methods: Sixty female rats were divided into five groups of 12 animals each: Normal Control (water), Test A (low ethanol), Control A (low iso), Test B (high ethanol) and Control B (high iso). Control Groups A and B received diets with the same amount of calories consumed by Test Groups A and B, respectively, with ethanol replaced by isocaloric amounts of carbohydrate. Four weeks prior to the end of the experimental period, half of the rats in each group were randomly assigned to receive a ligature on mandibular molar, whereas the other half of group was left unligated. At 8 weeks, the animals were sacrificed, and the specimens were processed to obtain decalcified sections. The area of periodontal ligament and/or bone loss in the furcation region of the first molars was histometrically measured in five sections per specimen (mm2). Results: Ethanol intake did not have effect on the alveolar bone loss in unligated teeth (p>0.05). However, in ligature-induced periodontitis, high value of calories associated with ethanol feeding enhanced the area of bone loss (p<0.05). Conclusions: The results of this study demonstrated that a low-ethanol diet did not affect the periodontium, while a high-ethanol diet may aggravate the progression of periodontitis, as demonstrated by the increased furcation region bone destruction in periodontal disease.
Keywords: Alveolar bone loss; Ethanol; Periodontitis; Rats